Exploring the Nutritional Profile and Cost of Plant-Based Milk Alternatives Compared with Dairy Milk in the UK with Consideration of Environmental Impact Data - Gemma K Nowson; Rosalind Fallaize; Kate E Earl (Current Developments in Nutrition)
Background: Plant-based milk alternatives (PBMA) are increasingly popular, driven by medical, environmental, or moralistic reasons or perceived health benefit. Objectives: This study aimed to compare the nutritional profile, cost, and environmental impact of all PBMA and dairy milk (DM) in the United Kingdom. Methods: Nutritional information, ingredients, and cost of PBMA (n = 191) and DM (n = 195) were systematically collected from the top 10 supermarkets. Published data on the environmental impact of foods were assessed. Milk was classified per 100 mL by energy (kcal), macronutrients (g), and micronutrients (mg, μg) and mean/median were compared between PBMA and DM. Further analysis stratified milks by DM fat profile. PBMA were categorized according to NOVA criteria. Cost per 1 L and environmental impact were compared for PBMA and DM. Results: PBMA with a similar fat profile to “semi-skimmed” milk had a significantly lower energy content (P < 0.001) and most (except coconut) had a significantly lower saturated fat content than DM. DM provided more protein, carbohydrate, total sugar, and salt and PBMA provided more fiber and total vitamin D. In total, 92% of nonorganic PBMA were fortified with ≥1 micronutrient; 87% with calcium, 34% iodine, 79% vitamin B12, and 56% vitamin B2. PBMA contained between 2% and 16.5% of the “main ingredient,” e.g. “oats.” Of nonorganic PBMA, 97% were classified as “ultraprocessed.” On mean, PBMA (£1.95/L) cost 64% more than DM (£1.19/L). Environmental analysis was conducted but not considered sufficiently robust to draw meaningful results (Appendix A). Conclusions: PBMA cannot be recommended as a nutritional replacement for DM, due to varying nutritional profiles. However, some PBMA will be more beneficial than others depending on an individual's health needs. Cow milk is cheaper than PBMA. Further understanding of the potential health impacts of consuming PBMA is warranted. There is a need for robust, primary research on the environmental impacts of foods.